MENGINTEGRASIKAN ETIKA KEILMUAN DALAM PENDIDIKAN: IMPLIKASI BAGI PENULISAN KARYA TULIS ILMIAH MODERN - Bahari, Priya Kusuma; Marianah, Dina; Sumarni, Tutin; Mas'ula, Siti; Pristiani, Riska (STKIP Persada Khatulistiwa Sintang, 2025)
Education today faces the challenge of integrating academic ethics into the learning process, particularly in scientific writing. This study aims to review the literature on the integration of academic ethics in the field of education and its implications for modern scientific writing. The research method employed is the Systematic Literature Review (SLR). Through this method, the study analyzes various sources of literature from relevant articles. A total of five international journal articles obtained from the Google Scholar database were used in this research. The analysis results indicate that the application of academic ethics not only improves academic quality but also shapes the character of writers to be responsible and ethical. These findings are expected to contribute to the development of better educational policies and encourage ethical scientific writing practices among researchers. Therefore, this article emphasizes the importance of integrating academic ethics as a foundation for creating a healthy and productive academic environment.